Analysis of the Czech and Slovak Different Strategic Choices Towards the Eurozone - Jiang Li (Romanian Journal of European Affairs)
Czechs and Slovaks lived in a common country from 1918 to 1992, and in May 2004 the Czech Republic and Slovakia joined the EU together; nevertheless, these two countries took different paths towards the Eurozone. On January 1, 2009 Slovakia became the 16th member state of the Eurozone, while the Czech Republic has not yet determined a specific timetable to enter the Eurozone. In this paper, our main objective is to answer the following questions: Why did the Czech Republic and Slovakia make different strategic choices on the issue of euro introduction? How could Slovakia, a country with unfavourable initial conditions of transformation, quickly achieve the full compliance of the Maastricht convergence criteria? How is Slovakia’s experience in the Eurozone? Compared with the Czech Republic, which has not introduced the euro, is the Slovak economic situation better or not? Which economic consequences did the Eurozone debt crisis bring to Slovakia and how does it affect the decision of the other Central European countries, including the Czech Republic, about euro adoption?